A new species of the family alycidae (Acari, endeostigmata) from southern Siberia, Russia - Uusitalo Matti (University of Tyumen, 2022)
A new species is described from southern Siberia, Tuva Republic, Russia: Amphialycus (Amphialycus) holarcticus sp. n. (Acari, Endeostigmata, Alycidae). This species can be recognized by its broad naso with longitudinally arranged striae; two pairs of cheliceral setae, posterior one being forked; three pairs of adoral setae; and a large number of genital setae. Two pairs of palpal eupathidia are close to each other, representing a kind of transitional form towards the fusion of the basal parts of eupathidia, observed in the subgenus Orthacarus.